Performance measures for small-bowel endoscopy: a European Society of Gastrointestinal Endoscopy (ESGE) Quality Improvement Initiative – Update 2025 - Sidhu, Reena; Shiha, Mohamed G.; Carretero, Cristina; Koulaouzidis, Anastasios; Dray, Xavier; Mussetto, Alessandro; Keuchel, Martin; Spada, Cristiano; Despott, Edward J.; Chetcuti Zammit, Stefania; McNamara, Deirdre; Rondonotti, Emanuele; Sabino, João; Ferlitsch, Monika; External Voting Panel; Elli, Luca; McAlindon, Mark E.; Murino, Alberto; Pennazio, Marco; Plevris, John; Rosa, Bruno; Sanders, David S. (Endoscopy, 2025)
Quality markers and patient experience are being implemented to ensure standardization of practice across gastrointestinal (GI) endoscopy procedures. The set benchmarks ensure high quality procedures are delivered and linked to measurable outcomes.There has been an increase in the demand for small-bowel endoscopy. In 2019, the European Society of Gastrointestinal Endoscopy (ESGE) embarked on setting performance measures for small-bowel endoscopy. This included major (key) and minor performance indicators for both small-bowel capsule endoscopy (SBCE) and device-assisted enteroscopy (DAE). These suggested quality indicators cover all procedure domains, from patient selection and preparation, to intraprocedural aspects such as pathology identification, appropriate management, the patient experience, and post-procedure complications. Since 2019, there has been an increase in published studies looking at different aspects of small-bowel endoscopy, including real-world data. This paper provides an update on the 2019 performance measures, considering the latest literature.